Fundamental Physics Practicum e-module to determine the value of the Earth's gravitational acceleration based on recorded experiments - Natalia Erna Setyaningsih; Agus Nu'man; Fifin Dewi Ratnasari; Danang Subarkah Hadi Kawuryan (Universitas Ahmad Dahlan, 2022)
The research aims to improve the effectiveness of fundamental physics practicum to determine the value of the Earth's gravitational acceleration, whether carried out online or offline.   This type of research is development research. The research was conducted using the 4D method: define, design, development, and disseminate. The product developed as a module contains a guidebook into an electronic module by integrating a practicum video (recorded experiment) that contains how to use the tools and practicum work steps. Data collection techniques are carried out by interviews and questionnaires. Questionnaires are given to a material, language and media experts to find out the validity of the e-module. Questionnaires are also given to lecturers who teach fundamental physics courses and students participating in introductory physics courses to find out the feasibility of e-modules. From the study, the average score of material, language and media experts was 89.08%, stating that the e-module was very valid. At the same time, the average score for the feasibility test is 89.38% which states that the e-module is very feasible. Thus, the development of a fundamental physics practicum e-module can increase the effectiveness of the fundamental physics practicum in determining the value of the Earth's gravitational acceleration.